2020
DOI: 10.1111/tpj.15003
|View full text |Cite
|
Sign up to set email alerts
|

Development and screening of EMS mutants with altered seed oil content or fatty acid composition in Brassica napus

Abstract: SUMMARY Brassica napus is an important oilseed crop in the world, and the mechanism of seed oil biosynthesis in B. napus remains unclear. In order to study the mechanism of oil biosynthesis and generate germplasms for breeding, an ethyl methanesulfonate (EMS) mutant population with ~100 000 M2 lines was generated using Zhongshuang 11 as the parent line. The EMS‐induced genome‐wide mutations in M2−M4 plants were assessed. The average number of mutations including single nucleotide polymorphisms and insertion/de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
6
25
0
Order By: Relevance
“…The frequency of non-G/C to A/T transitions increased correspondingly, and the frequency of indels increased to 21.56%. High-impact effects on gene function were also similar to the reported 0.52% in rapeseed (Tang et al, 2020). However, with EMS seed treatment, the frequency of G/C to A/T transition reached 86.5% in rapeseed (Shirasawa et al, 2016) and 68.4% in tomato (Tang et al, 2020).…”
Section: Pollen-ems Mutagenesis Facilitates Mutation Library Construc...supporting
confidence: 81%
“…The frequency of non-G/C to A/T transitions increased correspondingly, and the frequency of indels increased to 21.56%. High-impact effects on gene function were also similar to the reported 0.52% in rapeseed (Tang et al, 2020). However, with EMS seed treatment, the frequency of G/C to A/T transition reached 86.5% in rapeseed (Shirasawa et al, 2016) and 68.4% in tomato (Tang et al, 2020).…”
Section: Pollen-ems Mutagenesis Facilitates Mutation Library Construc...supporting
confidence: 81%
“…Former studies demonstrating EMS-induced random mutagenesis in Brassicaceae crops have reported a wide range of mutation frequencies between 1/12 kb to 1/447 kb [55; 56; 57; 34; 58; 59] . In this work, we screened the EMS-mutagenized population of the winter rapeseed ‘Express617’ developed by Harloff et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…NIRS analysis was performed by a Foss NIRSystems 5000 near‐infrared reflectance spectroscope to detect SOC, which was followed as previous report (Tang et al., 2020a ). FA and oil contents were analysed by GC‐MS as previous describe (Lu et al., 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 505 B.napus accessions collected from different research institutions were grown in Wuhan for two growth seasons (2012–2013 and 2013–2014). Mature open‐pollinated seeds of the natural population were harvested and desiccated for the analysis of SOC by a Foss NIRSystems 5000 near‐infrared reflectance spectroscope, and the polymorphic SNPs of BnaRGAs and BnaLEC1s were genotyped by genomic DNA re‐sequencing (Tang et al., 2020a ). The efficient Mixed‐Model Association eXpedited (EMMAX) analyses were used for genome‐wide association analysis.…”
Section: Methodsmentioning
confidence: 99%